'A different way to look at things': the development of consultancy in a residential service for children and young people - Andrew Kendrick (Scottish Journal of Residential Child Care)
The support of consultancy and the tasks associated with consultation are considered to play a vital role in the development of good practice in residential care and in safeguarding children and young people. Back in the 1970s, Berry (1975) recommended that all residential workers should have opportunities for support and consultation and 'every residential unit requires a special senior supporter who devotes himself (sic) to the staff without being directly responsible for the children... a consultant, counsellor, supervisor or therapist (but not an inspector)' (Berry, 1975, p. 134). More recently, however, Warner(1992) highlighted that too often staff in children's homes are left to cope with abused, disturbed and violent young people without access to the specialist psychiatric and psychological services that are needed (Warner, 1992, p. 144). He stressed the need for support from specialists in other agencies such as child psychiatrists and educational psychologists and for staff care schemes such asstress counselling (Warner, 1992, pp. 154-155). Over half the heads of units in the survey of residential establishments in Scotland felt they needed additionalsupport such as a specialist adviser, consultant or psychologist, and 'often such a specialist was required to provide a service both to residents and/or staff, suchas an independent counsellor' (Harvey, 1992, pp. 27-28).